PENGARUH PENAMBAHAN LARUTAN SUKROSA TERHADAP AKTIVITAS ANTIBAKTERI MINUMAN SINBIOTIK EKSTRAK CINCAU HIJAU SELAMA PENYIMPANAN PADA SUHU DINGIN - Samsul Rizal; Julfi Restu Amelia; Suharyono A S (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2019)
Sinbiotic drinks have a very acidic taste, so it is necessary to add sucrose solution to get the best taste. This study aims to determine the effect of adding 65% (v/v) sucrose solution to changes in antibacterial activity of green grass jelly synbiotic drinks during storage in cold temperatures. The finished green grass jelly synbiotic product was given two different treatments, namely the product without the addition of sucrose solution and product with the addition of 10% (v/v) of 65% (b/v) sucrose solution. The product was stored for 28 days at a cold temperature of ± 10oC. Observations were carried out every 7 days for antibacterial activity, pH, total acid, and total lactic acid bacteria. Antibacterial activity was evaluated using the agar diffusion method against pathogenic bacteria including Staphylococcus aureus, Salmonella sp., Bacillus cereus, and Eschericia coli. The results showed that the antibacterial activity, pH, and total lactic acid bacteria of green grass jelly synbiotic drinks both without and with the addition of 65% (b/v) sucrose as much as 10% (v/v) reduced during storage at cold temperatures, while total acid increases. There was no significant difference between the antibacterial activity and the characteristics of the green grass jelly synbiotic drink given 65% sucrose solution and without the addition of 65% sucrose solution. Thus the study concluded that the addition of 65% sucrose solution to increase the preference for the product did not significantly affect the change in antibacterial activity of the green grass jelly synbiotic beverage during storage in cold temperatures.